Evaluation of the safety and efficacy of surgery for radio-recurrent prostate cancer: a systematic review and meta-analysis - Zhu, Shengyu; Liu, Jianjiang; Zhong, Wei; Shen, Bin; Xu, Huali; Ni, Jiajing (Frontiers in Oncology, 2026)
BackgroundSurgery plays a critical role in managing radio-recurrent prostate cancer (PCa). This study aims to comprehensively review its effectiveness and associated severe complications.MethodsA thorough review of PubMed and EMBASE databases up to July 2024 was conducted, focusing on recurrence-free survival (RFS) with salvage surgery across various subgroups. Severe complications were also assessed using the Clavien-Dindo Scale (CDS). Survival curves were reconstructed using WebPlotDigitizer and a newly developed shiny application.ResultsForty-four studies were included, with 17 papers (2056 patients) contributing to survival curve reconstruction. Among 1654 patients treated with salvage surgery after eliminating duplicate cases, the median RFS was 63.9 months, with 2-, 3-, and 5-year rates of 65.6%, 59.3%, and 51.2%, respectively. Factors associated with better RFS included robot-assisted surgery [hazard ratio (HR):1.49, p < 0.001], lower rates of seminal vesicle invasion (SVI) (HR: 0.75, p = 0.006) and lymph node involvement (LNI) (HR: 0.74, p = 0.006), higher proportion of adjuvant androgen deprivation therapy (ADT) (HR: 2.96, p < 0.001), and higher values of pathological Gleason scores (GS) (≤7/≥8) (HR:1.30, p < 0.001). Severe complications (grade ≥ IIIa) occurred in 404 out of 2537 patients (15.9%, 95% CI: 14.5 to 17.4).ConclusionsThis study comprehensively assesses complications and conducts a pooled analysis of RFS for salvage surgery in radio-recurrent PCa. Robot-assisted surgery, lower rates of SVI and LNI, adjuvant ADT, and higher proportions of pathological GS ≤7 appear promising as prognostic factors for RFS. However, confirming these findings will necessitate randomized controlled trials due to low levels of evidence and study heterogeneity.